Pengaruh Persepsi Harga dan Self Control Terhadap Pembelian Impulsif Secara Online (Studi Kasus pada Mahasiswa Ekonomi dan Bisnis Universitas Bandar Lampung Tahun Angkatan 2019) - Habiburahman; Maharani (Jurnal EMT KITA, 2023)
The existence of the Internet has made everything easier, especially with the existence of various marketplaces. However, it turns out that this convenience tends to lead people to negative behavior. Especially for impulse purchases, they are subject to varying product prices and lack of self-control. Therefore, this study aims to prove the impact of price perception and self-control on impulse purchases made online by Bandar Lampung University economics students in the 2019 school year. The study population consisted of 365 students in the 2019 class of the Accounting and Management Programs at the Faculty of Economics, Bandar Lampung University. The sample for this study included 79 respondents, as random sampling was used to ensure an even distribution of study results. Multiple regression analysis was used for data analysis in this study. The results of this study show a significant negative effect between price perception and self-control over impulse purchases.